KENDALA PUBLIC SPEAKING DAN SOLUSI KECEMASAN KOMUNIKASI - Talalu, Taufik R (Dinamika Penelitian: Media Komunikasi Penelitian Sosial Keagamaan, 2022)
This article aims to understanding on types of public speaking barrier alongwith solutions for communication apprehension in students of Communicationand Islamic Department, IAIN Sultan Amai Gorontalo. A communicationapprehension as a public speaking barrier is depicted based on theunderstanding of perspectives of cognitive and behavioral as well as types ofcommunication apprehension. This research method is descriptive qualitative.The data obtained was collected from interviews and observations. The study’sfindings reveal that: 1) the communication apprehension experienced bystudents is driven by negative thoughts and trends to avoid public speaking;2) the types of communication apprehension experienced by students aretraitlike communication apprehension, context-based communicationapprehension, audience communication apprehension, and situationalcommunication apprehension; and 3) while preparing for a certain occasion,the communication apprehension experienced by the student is coped withshifting focus, having positive self-talk, doing exercise, and not memorizingmaterial. In addition, the students do role taking, breathing exercises, rightfoods eating, and body exercises before performing.